Collaborative filtering recommender systems: Methods, strengths and weaknesses - Marcel Schmidtke; Jannik Neeb; Thomas Wöhner (Verlag Ernst-Abbe-Hochschule Jena, 2025)
Recommender systems are indispensable in e-business due to the extensive product range and the large number of niche articles. Collaborative filtering (CF) algorithms play a central role in generating personalised recommendations. There are numerous CF approaches in the literature that have specific advantages and limitations. The aim of this article is to provide a comprehensive overview of the characteristics of model- and memory-based CF methods through a systematic literature analysis of 62 scientific papers. The analysis shows that memory-based approaches are convincing due to their simple implementation and interpretability but exhibit scaling problems as well as susceptibility to data sparsity and the cold start problem. Model-based methods, on the other hand, offer greater scalability and robustness against data sparsity, but require a more complex implementation, higher computing power and complicate the interpretation of results. – – Recommender-Systeme sind im E-Business aufgrund des umfangreichen Produktsortiments und der Vielzahl an Nischenartikeln unverzichtbar. Dabei nehmen Collaborative-Filtering-Algorithmen (CF) eine zentrale Rolle bei der Generierung personalisierten Empfehlungen ein. In der Literatur existieren zahlreiche CF-Ansätze, die spezifische Vorteile und Limitationen aufweisen. Ziel dieses Artikels ist es, durch eine systematische Literaturanalyse von 62 wissenschaftlichen Arbeiten, einen umfassenden Überblick über die Merkmale von model- und speicherbasierten CF-Methoden zu geben. Die Analyse zeigt, dass speicherbasierte Ansätze durch einfache Implementierung und Interpretierbarkeit überzeugen, jedoch Skalierungsprobleme sowie eine Anfälligkeit gegenüber Datenknappheit und Kaltstartproblemen aufweisen. Modellbasierte Methoden bieten dagegen eine höhere Skalierbarkeit und Robustheit gegenüber Datenknappheit, erfordern jedoch eine komplexere Implementierung, mehr Rechenleistung und erschweren die Ergebnis-interpretation.
Keywords: 330; Recommender systems; collaborative filtering; literature review; memory-based; model-based; Empfehlungssysteme; kollaboratives Filtern; systematische Literaturanalyse; speicherbasiert; modellbasiert